UNIT 1.36 Synthesis of S‐Adenosyl‐L‐Methionine Analogs with Extended Transferable Groups for Methyltransferase‐Directed Labeling of DNA and RNA. Issue 1 (1st March 2016) - Masevičius, Viktoras; Nainytė, Milda; Klimašauskas, Saulius
Abstract : S ‐Adenosyl‐L‐methionine (AdoMet) is a ubiquitous methyl donor for a variety of biological methylation reactions catalyzed by methyltransferases (MTases). AdoMet analogs with extended propargylic chains replacing the sulfonium‐bound methyl group can serve as surrogate cofactors for many DNA and RNA MTases enabling covalent deposition of these linear chains to their cognate targets sites in DNA or RNA. Here we describe synthetic procedures for the preparation of two representative examples of AdoMet analogs with a transferable hex‐2‐ynyl group carrying a terminal azide or amine functionality. Our approach is based on direct chemoselective alkylation of S‐adenosyl‐L‐homocysteine at sulfur with corresponding nosylates under acidic conditions. We also describe synthetic routes to 6‐substituted hex‐2‐yn‐1‐ols and their conversion to the corresponding nosylates. Using these protocols, synthetic AdoMet analogs can be prepared within 1 to 2 weeks. © 2016 by John Wiley & Sons, Inc.